2013
DOI: 10.1021/jp312750n
|View full text |Cite
|
Sign up to set email alerts
|

On the Validity of the Maximum Hardness Principle and the Minimum Electrophilicity Principle during Chemical Reactions

Abstract: Hardness and electrophilicity values for several molecules involved in different chemical reactions are calculated at various levels of theory and by using different basis sets. Effects of these aspects as well as different approximations to the calculation of those values vis-à-vis the validity of the maximum hardness and minimum electrophilicity principles are analyzed in the cases of some representative reactions. Among 101 studied exothermic reactions, 61.4% and 69.3% of the reactions are found to obey the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 163 publications
(89 citation statements)
references
References 93 publications
4
85
0
Order By: Relevance
“…67 The hardness value of the product is generally greater than that of the reactants for an exothermic process. 68 The HOMO−LUMO gap values of the bare BeCN 2 and BeNBO clusters are 6.78 and 7.96 eV, respectively. These values are improved significantly upon binding with Ng (Table 1).…”
Section: ■ Computational Detailsmentioning
confidence: 96%
“…67 The hardness value of the product is generally greater than that of the reactants for an exothermic process. 68 The HOMO−LUMO gap values of the bare BeCN 2 and BeNBO clusters are 6.78 and 7.96 eV, respectively. These values are improved significantly upon binding with Ng (Table 1).…”
Section: ■ Computational Detailsmentioning
confidence: 96%
“…14 Several pericyclic reactions were studied 15 to assess the applicability of electronic structure principles towards the prediction of Woodward-Hoffmann rules and it was concluded that these principles are consistent with the predictions of Woodward-Hoffmann rules on transition states (TSs) associated with the symmetry-forbidden disrotation and symmetry-allowed conrotation. In fact, most of the non-totally symmetric vibrations obey the MHP well due to the near constant value of chemical potential and external potential during nuclear displacements.…”
Section: Introductionmentioning
confidence: 94%
“…Hence, it reflects the electronic stability of a system. It may be noted that as HOMO-LUMO energy gap of a system is a measure of hardness, the stability is connected with the maximum hardness principle (MHP) [100][101][102]. The HOMO-LUMO energy gap in CB[6] is quite high (10.81 eV) reflecting its high stability.…”
mentioning
confidence: 99%